2020
DOI: 10.1177/0033294120961068
|View full text |Cite
|
Sign up to set email alerts
|

Talking to the Dead in the Classroom: How a Supposedly Psychic Event Impacts Beliefs and Feelings

Abstract: Paranormal beliefs (PBs) are common in adults. There are numerous psychological correlates of PBs and associated theories, yet, we do not know whether such correlates reinforce or result from PBs. To understand causality, we developed an experimental design in which participants experience supposedly paranormal events. Thus, we can test an event’s impact on PBs and PB-associated correlates. Here, 419 naïve students saw a performer making contact with a confederate’s deceased kin. We tested participants’ opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…(p. 241); 70% to 80% answered affirmatively. Recent studies confirmed that firsthand experiences of supposedly paranormal demonstrations were widely accepted as true and that such performances can enhance performance-related beliefs (Lan et al, 2018;Lesaffre et al, 2021), even more so in case of pre-existing paranormal beliefs (Lesaffre et al, 2021). Stage magic therefore provides us with a valuable tool to investigate the impact that misinformation has on people's beliefs.…”
Section: The Impact Of Pre-warning On False Beliefsmentioning
confidence: 83%
See 1 more Smart Citation
“…(p. 241); 70% to 80% answered affirmatively. Recent studies confirmed that firsthand experiences of supposedly paranormal demonstrations were widely accepted as true and that such performances can enhance performance-related beliefs (Lan et al, 2018;Lesaffre et al, 2021), even more so in case of pre-existing paranormal beliefs (Lesaffre et al, 2021). Stage magic therefore provides us with a valuable tool to investigate the impact that misinformation has on people's beliefs.…”
Section: The Impact Of Pre-warning On False Beliefsmentioning
confidence: 83%
“…Magicians' performances can perpetuate beliefs in psychic powers (Marks, 2000) or the existence of pseudo-psychological principles (Lan et al, 2018). Indeed, such magic performances often result in spectators truly believing in what they just saw (Lesaffre et al, 2018(Lesaffre et al, , 2021Mohr et al, 2019;Mohr & Kuhn, 2020). Back in 1944, Marcuse and Bitterman (1944) already used a classroom demonstration in which a magician used magic tricks to demonstrate fake paranormal abilities.…”
Section: The Impact Of Pre-warning On False Beliefsmentioning
confidence: 99%
“…A significant negative correlation emerged for jumping to conclusions, but only with the Traditional Religious Beliefs (TRB) subscale of the Rasch-devised RPBS [ 85 ]. A significant positive correlation was also found between TRB scores and self-report indices of jumping to conclusions as measured with the Cognitive Biases Questionnaire [ 118 , 119 ] (e.g., “imagine you hear that a friend is having a party and you have not been invited”, 1 = little or no inclination to jump to a premature conclusion, 2 = inclination to make a cautious inference, 3 = inclination to jump to a dramatic inference).…”
Section: Resultsmentioning
confidence: 99%
“…For example, one exhibit revealed that magicians can make objects vanish by surreptitiously (but in full view of the audience) dropping them behind the edge of a table top (Kuhn & Tatler, 2005), another exhibit explained the disappearance of an object by the magician concealing an object in his palm while pretending to throw it up in the air (Kuhn & Land, 2006). Other exhibits explored magic methods like memory misdirection (Ortega, Montañes, Barnhart, & Kuhn, 2018), forcing (Olson, Amlani, Raz, & Rensink, 2015;Olson, Amlani, & Rensink, 2012), and cold reading (Lan, Mohr, Hu, & Kuhn, 2018;Lesaffre et al, 2020;Olson, Demacheva, & Raz, 2015) can help induce illusory experiences. In these instances, the exhibition revealed the psychological mechanisms that underpin these principles, and in doing so arguably 'exposed' these methods to the exhibition visitors.…”
Section: Introductionmentioning
confidence: 99%